Teaching science through inquiry - Ng, Pearly * (Sunway University College, 2010)
Learning is a process of acquiring knowledge and skill through practice, training and accumulation of experience. Teaching is thus an act of imparting knowledge and skill. The most conventional way of teaching science has been through lecturing. In a typical lecture setting, the audience is expected to listen and follow a set of notes without much questioning. Such a method seems to contradict the learning of science, which builds on prior knowledge and advances through curiosity. As a result, this one-way transmission of knowledge has induced dry memorization and very little interest in exploring science by the students. The dullness in learning science could be due to the lack of development of quantitative and analytical skills that come with conventional teaching. This gives rise to the stereotypical perception that science is cryptic, difficult and can only be understood by very smart students. The National Science Teachers Association (NSTA) has suggested that science teachers employ the method of inquiry-based teaching to overcome the inefficacy of conventional teaching. Inquiry-based teaching is much more desirable and effective in teaching science subjects because it follows more closely the scientific method of experimentation. This paper aims to explore the potentials of assimilating inquiry-based teaching into the current conventional method. Hopefully by adopting a more effective teaching method, we can engage more learners in shaping the education they receive and inspire them to become the creators of knowledge themselves.